Pola Komunikasi pada Komunitas Dance Cover Elites Revolution Crew Bali - Siswanto Putri, Anisha Rahma; Purnawan, Ni Luh Ramaswati; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2021)
ABSTRACT “Elites Revolution Crew Bali is the oldest and still active K-Pop dance cover community in Bali. Elites Revolution Crew Bali was formed because they like K-Pop and have a hobby of dancing which was established on March 13, 2013. The purpose of this study was to explain the communication patterns in the dance cover community of Elites Revolution Crew Bali. This research uses descriptive qualitative research. Informants were selected using purposive technique. Data obtained through interviews and documentation study. The data analysis techniques used in the study were data reduction, data presentation and the final step to draw conclusions. The results of this study Elites Revolution Crew Bali uses two types of communication patterns in interaction, namely, the wheel communication pattern used during serious formal activities or meetings and the communication patterns of all channels used during informal, casual activities. Good communication has made Elites Revolution Crew Bali survive until now.”     Keywords : Communication Patterns, Dance Cover Community, K-Pop